Episodic alcohol exposure attenuates mesenchymal stem cell chondrogenic differentiation during bone fracture callus formation. (16th May 2022) - Eby, Jonathan M.; Sharieh, Farah; Azevedo, Jessica; Callaci, John J.
Abstract: Background: During bone fracture repair, mesenchymal stem cells (MSC) differentiate into chondrocytes and osteoblasts to form a fracture callus. Our laboratory previously reported that alcohol‐exposed rodents with a surgically created tibia fracture display deficient fracture callus formation and diminished signs of endochondral ossification characterized by the absence of chondrocytes and mature hypertrophic chondrocytes, suggesting that alcohol may inhibit MSC differentiation. These findings led to our hypothesis that alcohol exposure inhibits mesenchymal stem cell chondrogenic differentiation within the developing fracture callus. Methods: In the present study, we utilized a lineage‐tracing approach to determine which stage(s) of chondrogenic differentiation are affected by alcohol exposure. We utilized lineage‐specific reporter mice to determine the effects of alcohol on MSC and early and late chondrogenic cell frequencies within the fracture callus. In addition, serially sectioned slides were stained immunofluorescently and immunohistochemically and quantified to determine the effect of alcohol on cell proliferation and apoptosis, respectively, within the fracture callus of alcohol‐administered rodents. Results: Alcohol‐administered rodents had a reduced fracture callus area at 4, 6, and 9 days postfracture. Alcohol had no effect on apoptosis in the fracture callus at any of the examined timepoints. Alcohol‐administered rodents had significantly fewer proliferative cells in the fracture callus at 9 days postfracture, but no effect on cell proliferation was observed at earlier fracture callus timepoints. Alcohol‐administered rodents had reduced Collagen2a1‐ and Collagen10a1‐expressing cells in the developing fracture callus, suggesting that alcohol inhibits both early chondrogenic differentiation and later chondrocyte maturation during fracture callus development. Conclusion: The data suggest that alcohol could affect normal fracture healing through the mitigation of MSC chondrogenic differentiation at the callus site. Abstract : Alcohol abuse increases the incidence of fracture nonunion. We utilized transgenic reporter mice with a tibia fracture to demonstrate that acute alcohol exposure has profound effects on the cartilaginous fracture callus, including reductions in callus area and Col2a1 2 and Col10a1‐expressing cells, while overall callus cell number, cell proliferation and apoptosis are unaffected by alcohol. This data suggests that alcohol‐related deficient fracture healing may be driven in part by an underlying perturbation of MSC differentiation towards a chondrogenic lineage.